Post Surgical Neglected Idiopathic Triple Curve Scoliosis with Neuromuscular and Respiratory Disorders - Rahmatika; Rudy Handoyo; Tanti Ajoe Kesoema (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: About 75-85% of cases of scoliosis are idiopathic, with unknown cause whose ratio between men and women is 1: 8. In severe scoliosis, many disorders may occur such as muscle imbalance, pain, muscle weakness, degenerative joint disease, decreased cardiovascular capacity, and neurological disorders.Case Presentation: We reported a 14-year-old boy patient post posterior instrumentation and fusion surgery e.c neglected idiopathic triple curve scoliosis with neuromuscular complications such as weakness in upper and lower limbs causing disruption in hand functions and ambulation disorders, and respiration disorders such as shortness of breath, especially when walking in long-distance or running.The rehabilitation program consisting of exercise in the pool, fine motor exercise, activity of daily living (ADL) exercise, chest expansion exercise, and orthotic administration, which aims to support therecovery of patients to full function as early as possible.Conclusion: After 2 months, the patient showed slight improvement in functional, ambulation, and hand function due to non-routine exercise at the hospital.